Manajemen Risiko Default Pada Pengguna Kartu Kredit Menggunakan Framework NIST 800-30 - Agus Eko Musantono; Atina Khoiron Nisa; Ashlih Qurota A’Yuni; Haniful Umam (Faculty of Computer Science, University of Jember, 2022)
The emergence of credit cards as one of the earliest fintech technologies capable of providing benefits to customers or users, the maturity of the system in its application is very important because it is related to user data. Several problems arise including carding crimes or problems from the users themselves. This study aims to determine demographic factors with the effect of using credit cards. Demographic factors (gender, age, marital status and academic) are related to usage activities as well as in paying off credit card bills. Quantitative research is carried out using available datasets. from the dataset will be processed and the required part will be taken. By using the NIST 800-30 framework, it is hoped that it can assist in risk management and assessment, then it will lead to risk tendencies in using credit cards. The final result of the study show that demographic factors including age, academic and marital status able to show the affect activities in paying credit card bills and the reliability of the credit card issuer's system can reduce the impact of default on credit card users.